Perivascular Stem Cells Diminish Muscle Atrophy and Retain Viability in a Rotator Cuff Tear Model. Issue 7 (18th July 2016) - Eliasberg, Claire; Jensen, Andrew; Dar, Ayelet; Kowalski, Tomasz J.; Murray, Iain; Khan, Adam Z.; Natsuhara, Kyle; Garagozlo, Cameron; McAllister, David R.; Petrigliano, Frank A.
Objectives: Rotator cuff tears (RCTs) are a common cause of shoulder pain and often necessitate surgical repair. Muscle changes including atrophy, fibrosis, and fatty degeneration can develop after RCTs, which may compromise surgical repair and clinical outcomes. Lipoaspirate-derived human perivascular stem cells (PSCs) have demonstrated myogenic and angiogenic potential in other small animal models of muscle injury. We hypothesized that the administration of PSCs following massive RCTs may help to diminish these muscle changes in a small animal model. Methods: A total of 90 immunodeficient mice were used (15 groups, N=6). Each was assigned to one of three surgical groups: i) sham, ii) supraspinatus and infraspinatus tendon transection (TT), or iii) TT and suprascapular nerve denervation (TT+DN). PSCs were harvested from human lipoaspirate and sorted using fluorescence-activated cell sorting into small blood vessel residing pericytes (CD146+ CD34- CD45- CD31-) and large blood perivascular adventitial cells (CD146- CD34+ CD45- CD31-). Mice received either a) no injection, b) saline injection, c) pericyte injection, or d) adventitial cell injection at the time of the index procedure or at two weeks following index surgery. The supraspinatus muscles were harvested six weeks after the index procedure. Muscle atrophy was assessed by measuring percent wet muscle weight change for each sample. Muscle fiber cross-sectional area (CSA), fibrosis, and fatty degeneration were analyzed using Image J™. Additionally, pericytes and adventitial cells were transduced with a luciferase-containing construct. Animals were given injections of luciferin and imaged using IVIS to track in vivo bioluminescence following injections to assess cell viability. Results: Treatment with PSC injection after TT resulted in less wet weight loss and greater muscle fiber CSA than control groups (P<0.05). The TT+DN groups treated with PSC injections two weeks post-op also had less muscle weight loss and greater muscle fiber CSA than their respective control groups. The TT+DN groups treated with PSC injections at the time of surgery demonstrated no differences in weight loss, but had greater muscle fiber CSA than their respective controls. There was no difference in fibrosis between the TT groups. However, TT+DN groups treated with pericyte injections at both time points and adventitial cell injections two weeks post-op had less fibrosis than TT+DN controls. There was less fatty degeneration in the TT groups treated with pericyte injections at both time points and adventitial cells at the time of surgery compared to matched controls. There were no differences in the amount of fatty degeneration between the TT+DN groups. Bioluminescence imaging demonstrated viability of the injected cells at three weeks following injections (Figure 1). Conclusion: Our findings demonstrate significantly less muscle atrophy in the groups treated with PSC injections compared to respective controls for both TT and TT+DN procedures. These results suggest that the use of PSCs may have a role in the prevention of muscle atrophy by aiding in the maintenance of muscle bulk without leading to increased fibrosis or fatty infiltration. Additionally, bioluminescence data suggests that these cells maintain viability and engraft within the native muscle to improve muscle bulk. Improved muscle quality in the setting of rotator cuff tears may increase the success rates of rotator cuff repair and lead to superior clinical outcomes.